Utilization of Piji Palm [Pinanga coronata (Blume) Blume] by People Around Baturraden Botanical Garden, Banyumas Regency, Central Jawa - Solihah, Saniyatun Mar'atus; Atria, Mega; Witono, Joko Ridho (Elkawnie, 2025)
Abstract: Baturraden Botanical Garden is an ex-situ plant conservation area at the foot of Mount Slamet, Central Java. People around this botanical garden continue to live traditional lives, utilizing plants in their daily lives, including the Piji palm (P. coronata). However, knowledge regarding the use of the P. coronata palm in Indonesia has never been reported; therefore, it needs to be explored to increase ethnobotanical information. This study aimed to obtain utilization information from P. coronata in daily life. The study was conducted in April 2024 in the area around Baturraden Botanical Garden, Baturraden District, Banyumas Regency, Central Java. Information was collected using an interview method using a snowball sampling technique with 37 respondents who were deemed to have broad and specific knowledge of the use of P. coronata. The data obtained was analyzed descriptively and qualitatively. The results showed that people around the Baturraden Botanical Garden utilize P. coronata from nature (growing wild) to support daily life, which is divided into 8 (eight) aspects, including traditional medicine (fruit and shoot parts), ornamental/decorative plants (whole plants and leaves), environmental role (whole plants, stems, and leaves), building materials (stems and leaves), animal feed (leaves and fruit), food ingredients (stem shoots), ritual/culture (leaves and fruit), and handicrafts/tools/toys (stems, leaves, and fruit). The three parts of P. coronata that have high potential and economic value in the industry include the whole plant (ornamental/decorative plants), leaves (crafts), and stem shoots (traditional medicine and food). Abstrak: Kebun Raya Baturraden merupakan kawasan konservasi tumbuhan ex situ yang berada di kaki Gunung Slamet, Jawa Tengah. Kehidupan masyarakat di sekitar kebun raya ini masih tradisional, sehingga pemanfaatan tumbuhan dalam kehidupan sehari-hari masih dilakukan seperti pemanfaatan palem Piji (P. coronata). Namun demikian, pengetahuan terkait pemanfaatan palem P. coronata di Indonesia belum pernah dilaporkan, maka dari itu perlu digali untuk menambah informasi etnobotaninya. Studi ini bertujuan untuk mendapat informasi pemanfaatan P. coronata oleh masyarakat di sekitar Kebun Raya Baturraden dalam kehidupan sehari-hari. Penelitian dilakukan pada bulan April 2024 di daerah sekitar Kebun Raya Baturraden, Kecamatan Baturraden, Kabupaten Banyumas, Jawa Tengah. Pengumpulan informasi dilakukan dengan metode wawancara dengan teknik snowball sampling terhadap 37 orang responden yang dianggap memiliki pengetahuan yang luas dan spesifik dari pemanfaatan palem P. coronata. Data yang diperoleh dianalisis secara deskriptif dan kualitatif. Hasil menunjukkan bahwa masyarakat di sekitar Kebun Raya Baturraden memanfaatkan P. coronata dari alam (tumbuh liar) untuk mendukung kehidupan sehari-hari yang terbagi dalam 8 (delapan) aspek, antara lain: pengobatan tradisional (bagian buah dan umbut), tanaman hias/dekorasi (tumbuhan utuh dan daun), peran lingkungan (tumbuhan utuh, batang, dan daun), bahan bangunan (batang dan daun), pakan ternak (daun dan buah), bahan pangan (umbut), ritual/budaya (daun dan buah), dan kerajinan tangan/alat/mainan (batang, daun, dan buah). Tiga bagian P. coronata yang memiliki potensi dan nilai ekonomi yang tinggi dalam industri antara lain: tumbuhan utuh (tanaman hias/dekoratif), daun (kerajinan), dan umbutnya (obat tradisional dan makanan).